Smokeless tobacco excise taxes in the US: Standardizing the measurement for empirical analysis - Yanyun He; Zezhong Zhang; Qian Yang; Ce Shang (Preventive Medicine Reports)
Introduction: The effect of smokeless tobacco (SLT) taxes on SLT use has received relatively little research attention in the US compared to the extensive focus on cigarette and e-cigarette taxation. The scarcity of SLT literature is partially due to the complexities of SLT taxes and the lack of standardized taxes. While some states imposed specific taxes based on the weight of the products, others imposed ad valorem taxes. These two types of tax schemas are not directly comparable, further complicating analysis. Objective: We standardize SLT taxes into two measures: first, we convert ad valorem taxes to specific taxes so that both taxes are expressed in $/ounce; second, we convert specific taxes to ad valorem taxes so that both taxes are measured as % of the wholesale price. Methods: We extracted sales-weighted retail prices from the Nielsen Retail Scanner Data between 2006 and 2020. We developed a method to standardize SLT taxes. Results: Overall, the standardized SLT taxes exhibit a steadily increasing trend. In the fourth quarter of 2020, the average specific tax for chewing tobacco, moist snuff, dry snuff, and snus was $0.36, $0.91, $0.74, and $1.27 per ounce, respectively. The average ad valorem tax for chewing tobacco, moist snuff, dry snuff, and snus was 57.4 %, 47.5 %, 42.6 %, and 38.8 % of wholesale prices, respectively. Conclusions: The SLT tax data provided here can serve as a valuable tool for policymakers in determining and refining SLT tax rates, further allowing future studies to understand their impacts on SLT use and related disparities.